Low serm Fibroblast Growth Factor-21 levels is not associated with Carotid intima-media thickness in acromegaly patients - YAVUZ, DİLEK (My University, 2022)
Introduction Elevated fibroblast growth factor-21 (FGF-21) levels are related to carotid intima-media thickness (CIMT), a well-established marker of atherosclerosis. Acromegaly has also been linked to increased CIMT. There has been no data considering the association between FGF-21 levels and atherosclerosis in acromegaly patients. This study aimed to evaluate FGF-21 levels and CIMT in acromegalic patients in relation to atherosclerotic complications. Design Case-control study. Materials and methods The study group included 70 acromegaly patients and 72 healthy volunteers from the Department of Endocrinology and Metabolism Disease, Marmara University Medical School. FGF-21, growth hormone, insulin-like growth factor I, lipids, glucose, insulin levels were assessed. CIMT was measured from the common carotid artery wall on B-mode ultrasound. Results Median FGF-21 levels were significantly lower in the acromegaly group than in the control group. CIMT was higher in acromegaly patients compared to controls. Although there was no correlation between FGF-21 levels and CIMT in patients with acromegaly, a positive correlation was found between high-density lipoprotein-cholesterol and FGF-21 levels. Glucose metabolic markers were the determining factors of the FGF-21 levels in acromegaly patients. Conclusion Our study is the first to examine the relationship between serum FGF-21 levels and atherosclerosis in acromegaly patients. The lower serum FGF-21 levels in acromegaly subjects might be associated with the improving effects of growth hormone on liver fat. Acromegaly was linked to higher CIMT, but there was no correlation between FGF-21 levels and CIMT. The role of FGF-21 in acromegaly as a marker of atherosclerosis requires additional research.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); Endocrinology; Endocrine and Autonomic Systems; Endocrinology, Diabetes and Metabolism; Life Sciences; Acromegaly; Atherosclerosis; FGF-21; IGF-1; Carotid intima-media thickness; Cardiovascular disease; DIABETES-MELLITUS; FACTOR-I; HORMONE; LIVER; ATHEROSCLEROSIS; TRANSCRIPTION; PLAQUE; GENE